ADHD Spectrum among Female Dental Students: An Observational Study at Watim Medical and Dental Hospital, Rawat - Khan, Meher Moin; Rashid, Noor Liza; Waqar, Zaid; Masood, Barrira; Zulfiqar, Shagoofa; Jalbani, Ariba (Journal of Neonatal Surgery, 2025)
Objective: To determine the prevalence and range of Attention Deficit Hyperactivity Disorder (ADHD) traits among female dental students at Watim Medical and Dental Hospital, Rawat. Methods: An observational cross-sectional study was conducted from February 2025 to July 2025, at the Department of Community and Preventive Dentistry Watim Medical and Dental Hospital, Rawat. The Adult ADHD Self-Report Scale (ASRS-v1.1), which has been validated, was administered to the 120 enrolled female dental students. The outcome variables were the prevalence of the different types of spectrum ADHD (inattentive, hyperactive/impulsive, and combined) as well as severity (mild, moderate, severe) and variables of study demographics which included age, year of study, residence status (hostelite/day scholar), and academic performance. Descriptive data analysis was done and results were presented in tabulated form. Results: 112 of the 120 participants completed the questionnaire, which translates to a 93.3% response rate. The prevalence of ADHD traits was 28.6% (n=32), and the most prevalent subtype was inattentive (53.1%), followed by combined (31.2%) and hyperactive/impulsive (15.6%). The ADHD traits were markedly prevalent in the first and second year students as compared to the final year students. Hostelite students showed a higher prevalence (34.4%) as compared to day scholars (22.2%). Conclusion: A considerable number of female dental students showed tendencies towards the ADHD spectrum, especially the inattentive variant. This highlights the importance of tailored screenings, proactive counseling, and the implementation of appropriate academic frameworks. These measures should be instituted within the wider healthcare and dental education frameworks